Acute Obstructive Hydrocephalus Due to Cysticercosis During Pregnancy - Ronald M. Ramus; Mark Girson; Diane M. Twickler; George D. Wendel (Hindawi Limited, 1994)
Conclusion: This case describes an uncommon presentation of neurocysticercosis that should be considered in gravidas with acute mental status changes.